The assessments of hierarchical 3D spatial data in an urban environment. Issue 1 (2nd January 2018) - Shih, Naai-Jung; Chen, Chien-Wei; Tzeng, Shih-Cheng
ABSTRACT: Urban fabric usually specifies the physical presence of existing structures. Examination of both permanent and temporary structures helps to understand the specific inconsistency occurring within the framework. This study applied the methodology in reverse engineering to verify the dynamic nature of urban fabric by the progress of development in Taipei, Taiwan. As-built urban fabric scans were used to identify inconsistencies from urban scale to building façade and street lamps for quantitative analysis purpose. An assessment to spatial data hierarchy is achieved through the comparison to a detailed level. The methodology was approached using different hierarchies of scan data as organized in terms of general scans of the entire site from roof level and focused scans on selected façade on street level. The data include the point clouds retrieved in Leica's scan worlds and Faro's scans, with selected regions using Asus Xtion Pro. A systematic approach was made for such inspections, in BIM 500 level, using a publicly accessible CAD platform. By referring to the original BIM or GIS, the identification of different parts is outlined for measurement or evaluation. The cross-reference base is created, and can refer to urban chronological development, local update information, construction quality or the misalignment of objects or facilities like street lamps. GRAPHICAL ABSTRACT: